OIL AS POLITICAL WEAPON - Mariana, BUICAN (Strategii Manageriale, 2013)
Oil (called by some black gold) has not always been as coveted and used, but only in the last hundred years has established itself as a highly sought after as an indispensable proper functioning of modern economic activity that an important factor in international politics. International oil regime has changed in the last decades. In 1960, oil regime was a private oligopol which had links with governments main consuming countries. By then the price of a barrel of oil was two U.S. dollars and seven major transnational oil companies decided the amount of oil that will be produced. Meanwhile the world region with the largest oil exports were more strongly expressed nationalism and decolonization. Result, it was so in the late 60s in the region occur independent states. They have created an organization aim of this resource to their advantage - OPEC (Organization of Petroleum Exporting Countries). Thus since 1973 there have been changes in the international regime governing oil field, namely producing countries were fixed production rate and price. After this time the oil weapon has become increasingly important in the management of international relations. Oil influenced the great powers to Middle East conflicts that occurred in the last century, but their attitude about the emergence of new sources of oil outside OPEC. In the late 90's, Russia has become a major supplier of oil to the West.